Mekanisme Mediasi dalam Penyelesaian kontrak Perjanjian Ketenagakerjaan di Indonesia - Nur Hayati; Hilyatun Nisak; Siti nur Azizah; M.Misbahussuduri; Firza Agung Prakoso (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Employment agreements are essential legal instruments that regulate the rights and obligations of workers and employers in industrial relations, aiming to ensure legal certainty and balance. In practice, however, the implementation of employment contracts often faces challenges such as differing interpretations, unequal bargaining positions, and inconsistent application of labor regulations. These issues require an effective and constructive dispute resolution mechanism that can address contractual problems while preserving employment relationships. In the Indonesian labor law system, mediation is recognized as a key non-litigation mechanism facilitated by government-appointed mediators to help parties reach mutually acceptable solutions. This study examines the mediation mechanism for resolving employment agreement disputes in Indonesia and analyzes its role as an alternative to court proceedings that emphasizes deliberation, efficiency, and cooperation. Using a normative legal research method with statutory and conceptual approaches, the study analyzes relevant labor laws, mediation regulations, and legal doctrines through a comprehensive literature review. The findings show that mediation is conducted through structured stages, including dispute registration with labor authorities, mediator appointment, facilitated negotiations, and the formulation of agreements or written recommendations. Mediation effectively promotes consensual solutions, reduces procedural complexity, and encourages cooperative communication. It also supports the preservation of harmonious and sustainable employment relationships by prioritizing consensus over adversarial processes. Strengthening mediator competence and improving legal awareness among workers and employers are therefore crucial to optimizing the effectiveness of mediation in resolving employment agreement disputes in Indonesia.